(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Background: Nurses are increasingly using information and communication technologies (ICTs) to provide high-quality healthcare. The manner that nurses plan, provide, record, and evaluate clinical care can all be altered by their use of ICTs. Aim: This research aimed to create a comprehensive picture of the reviews. Results: The practicing environment for nurses, nursing procedures, satisfaction with work, and nursing-sensitive results were the main results. The viewpoints of nurses regarding their level of satisfaction or discontent with ICTs comprised the additional results. Method: A comprehensive examination was conducted on 20 studies or descriptions to determine whether they were eligible and 10 publications’ complete texts were obtained for in-depth analysis. 10 reviews that were released during 2018 - 2023 were determined to be eligible. Conclusion: ICTs significantly influence nursing care themes like time management, patient care, documentation, information quality, nurse autonomy, collaboration, competencies, patient-patient relationships, evaluations, treatment planning, patient teaching, communication, care coordination, satisfaction, comfort, life satisfaction, empowerment, and functional status.